2021
DOI: 10.3390/ijms22136954
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baccharin Isolated from Brazilian Green Propolis on Adipocyte Differentiation and Hyperglycemia in ob/ob Diabetic Mice

Abstract: Propolis is a honeybee product with various biological activities, including antidiabetic effects. We previously reported that artepillin C, a prenylated cinnamic acid derivative isolated from Brazilian green propolis, acts as a peroxisome proliferator-activated receptor γ (PPARγ) ligand and promotes adipocyte differentiation. In this study, we examined the effect of baccharin, another major component of Brazilian green propolis, on adipocyte differentiation. The treatment of mouse 3T3-L1 preadipocytes with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Other possible mechanisms are improved insulin sensitivity and increased glucose uptake (Sakai et al, 2017). reported that there was an increase in GLUT4 expression and decrease in glucose levels, and associated with this, an increase in adiponectin levels was observed, directly related to a decrease in adipose tissue accumulation (Watanabe et al, 2021). , 1998;Bischoff et al, 1999).…”
Section: Evidences From In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other possible mechanisms are improved insulin sensitivity and increased glucose uptake (Sakai et al, 2017). reported that there was an increase in GLUT4 expression and decrease in glucose levels, and associated with this, an increase in adiponectin levels was observed, directly related to a decrease in adipose tissue accumulation (Watanabe et al, 2021). , 1998;Bischoff et al, 1999).…”
Section: Evidences From In Vivo Studiesmentioning
confidence: 99%
“…The main results are shown in Table 1. Experiments using different animal models have demonstrated beneficial effects of green propolis in the treatment and prevention of diseases such as gastric ulcer (Costa et al, 2018;Costa et al, 2019;Costa et al, 2020), colitis (Mariano et al, 2018Suzuki, 2019), drug intoxication (36) (Tsuchiya et al, 2018), cancer (Doi et al, 2017;Gastaldello et al, 2021), sepsis (Silveira et al, 2021), acute inflammation (Ferreira et al, 2021), infection (de L Paula et al, 2022, oral mucosal irritation (Furukawa et al, 2021), obesity (Sakai et al, 2017;Chen et al, 2022), diabetes (Watanabe et al, 2021), retinal injury (Park et al, 2020), asthma (Piñeros et al, 2020;Martins et al, 2021) and allergic rhinitis (Shaha et al, 2018). In these studies, it was observed that the administration of green propolis and its components favored the defense of the gastric mucosa by promoting an increase in the mucus layer.…”
Section: Evidences From In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Propolis, a resinous material produced by honeybees, has been widely used in TCM [21] and is bene cial to a variety of body systems [22]. Propolis has been analyzed mainly by RPLC [23], and has not yet analyzed by NPLC.…”
Section: Separation Of Propolismentioning
confidence: 99%
“…In diabetic ob/ob mice, the intraperitoneal administration of baccharin significantly improved blood glucose levels. These results suggest that baccharin has a hypoglycemic effect on glucose metabolic disorders, such as type 2 diabetes mellitus [ 9 ]. Capsaicin in chili peppers has potential benefits for the reduction in glucose metabolism disorders and acts through the activation of transient receptor potential cation channel subfamily V member.…”
mentioning
confidence: 99%